Impact of environment and social gradient on Leptospira infection in urban slums. - Renato B Reis; Guilherme S Ribeiro; Ridalva D M Felzemburgh; Francisco S Santana; Sharif Mohr; Astrid X T O Melendez; Adriano Queiroz; Andréia C Santos; Romy R Ravines; Wagner S Tassinari; Marília S Carvalho; Mitermayer G Reis; et al. (Public Library of Science (PLoS), 2008)
Leptospirosis has become an urban health problem as slum settlements have expanded worldwide. Efforts to identify interventions for urban leptospirosis have been hampered by the lack of population-based information on Leptospira transmission determinants. The aim of the study was to estimate the prevalence of Leptospira infection and identify risk factors for infection in the urban slum setting.We performed a community-based survey of 3,171 slum residents from Salvador, Brazil. Leptospira agglutinating antibodies were measured as a marker for prior infection. Poisson regression models evaluated the association between the presence of Leptospira antibodies and environmental attributes obtained from Geographical Information System surveys and indicators of socioeconomic status and exposures for individuals. Overall prevalence of Leptospira antibodies was 15.4% (95% confidence interval [CI], 14.0-16.8). Households of subjects with Leptospira antibodies clustered in squatter areas at the bottom of valleys. The risk of acquiring Leptospira antibodies was associated with household environmental factors such as residence in flood-risk regions with open sewers (prevalence ratio [PR] 1.42, 95% CI 1.14-1.75) and proximity to accumulated refuse (1.43, 1.04-1.88), sighting rats (1.32, 1.10-1.58), and the presence of chickens (1.26, 1.05-1.51). Furthermore, low income and black race (1.25, 1.03-1.50) were independent risk factors. An increase of US$1 per day in per capita household income was associated with an 11% (95% CI 5%-18%) decrease in infection risk.Deficiencies in the sanitation infrastructure where slum inhabitants reside were found to be environmental sources of Leptospira transmission. Even after controlling for environmental factors, differences in socioeconomic status contributed to the risk of Leptospira infection, indicating that effective prevention of leptospirosis may need to address the social factors that produce unequal health outcomes among slum residents, in addition to improving sanitation.